Chemical instrumental analysis versus human evaluation to measure sensory properties of dairy products: What is fit for purpose?. (October 2021) - Andrewes, Paul; Bullock, Shannon; Turnbull, Robyn; Coolbear, Tim
Abstract: Human sensory analysis is often simplistically and erroneously labelled "subjective"; this is then used to justify the attempted application of a range of instrumental methods to achieve the same purported measurement end points. However, there are no instrumental substitutes for human sensory analysis to measure human perception. In this review, fundamental considerations for any analyses are first presented as generic context. Mechanics of sensory measurement are then briefly explained with a focus on the key compound classes in dairy. Sensory analysis needs in new product development are outlined, and the fitness for purpose of chemical instrumental analysis versus human sensory analysis explained. Measurement accuracy as a criterion in decision making and issues and challenges encountered when proposing chemical measurements to complement or replace sensory measurements are described. Finally, what chemical analysis has yet to achieve to even begin to challenge human sensory analysis as an objective measurement tool is considered.